Paradygmat jako podstawa normalnego uprawiania nauki: nauki społeczne a przyrodoznawstwo. Ujęcie Thomasa Samuela Kuhna = Paradigm as simple of normal science practicing: social and natural sciences by Thomas Samuel Kuhn conception - Jankowski, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Article aims to present how Kuhn behold the fundamental difference between the social sciences (especially sociology) and mathematical natural science (mainly physics, astronomy and chemistry) as well as to the issue they treated representatives of the social sciences. The first two parts represent the Kuhn?s understanding of paradigm and practicing normal science. In the third part of Kuhn?s insights about the nature of social theory compare with what think about this social scientists.
Keywords: Kuhn, Thomas Samuel (amerykański fizyk, historyk, filozof; 1922-1996); przyrodoznawstwo; nauki społeczne; socjologia; paradygmat; protoparadygmat; wspólnota uczonych; nauka normalna; natural science; social sciences; sociology; paradigm; protoparadigm; scientific community; normal science